Connecting dysbiosis, bile-acid dysmetabolism and gut inflammation in inflammatory bowel diseases. Issue 4 (19th September 2012) - Duboc, Henri; Rajca, Sylvie; Rainteau, Dominique; Benarous, David; Maubert, Marie-Anne; Quervain, Elodie; Thomas, Ginette; Barbu, Véronique; Humbert, Lydie; Despras, Guillaume; Bridonneau, Chantal; Dumetz, Fabien; et al.
Abstract : Objective: Gut microbiota metabolises bile acids (BA). As dysbiosis has been reported in inflammatory bowel diseases (IBD), we aim to investigate the impact of IBD-associated dysbiosis on BA metabolism and its influence on the epithelial cell inflammation response. Design: Faecal and serum BA rates, expressed as a proportion of total BA, were assessed by high-performance liquid chromatography tandem mass spectrometry in colonic IBD patients (42) and healthy subjects (29). The faecal microbiota composition was assessed by quantitative real-time PCR. Using BA profiles and microbiota composition, cluster formation between groups was generated by ranking models. The faecal BA profiles in germ-free and conventional mice were compared. Direct enzymatic activities of BA biotransformation were measured in faeces. The impact of BA on the inflammatory response was investigated in vitro using Caco-2 cells stimulated by IL-1β. Results: IBD-associated dysbiosis was characterised by a decrease in the ratio between Faecalibacterium prausntizii and Escherichia coli . Faecal-conjugated BA rates were significantly higher in active IBD, whereas, secondary BA rates were significantly lower. Interestingly, active IBD patients exhibited higher levels of faecal 3-OH-sulphated BA. The deconjugation, transformation and desulphation activities of the microbiota were impaired in IBD patients. In vitro, secondary BA exerted anti-inflammatory effects, but sulphation of secondary BAs abolished their anti-inflammatory properties. Conclusions: Impaired microbiota enzymatic activity observed in IBD-associated dysbiosis leads to modifications in the luminal BA pool composition. Altered BA transformation in the gut lumen can erase the anti-inflammatory effects of some BA species on gut epithelial cells and could participate in the chronic inflammation loop of IBD.